Características de la sonrisa en niños con normoclusión (2015)
ABSTRACT: In assessing children’s smile, a gingival smile is usually accepted as normal, but there is no scientific evidence to support this statement. The goal of this research project was to describe the structural characteristics of posed unforced smile in children with normal occlusion in deciduous and mixed dentition. Methods: a cross-sectional study in 122 children aged 3 to 12 years with normal occlusion. Each kid was recorded a video clip and taken a photogram in unforced posed smile, which was used to quantify and describe smile variables. These variables were compared by gender and dentition type: the quantitative variables were analyzed with one-way ANOVA test and Student’s t test, and the qualitative variables with Pearson’s chi-squared test, using a significance level of 0.05. Results: the soft tissues evaluated in smile showed significant differences between deciduous dentition / early mixed dentition and silent mixed dentition / late dentition. These values were lower in females. There was a prevalence of high smile in deciduous dentition and early mixed dentition, and medium smile in silent mixed dentition and late mixed dentition. 89.3% of children had a matching smile arch. The smile rate was proportional among the dentition stages evaluated and between males and females. Conclusions: the high smile is predominant among child patients in early deciduous dentition and mixed dentition, and gingival exposure reduces as kids grow.